Increased circulating conjugated primary bile acids are associated with hyperandrogenism in women with polycystic ovary syndrome. Issue 189 (May 2019) - Zhang, Bingjie; Shen, Shanmei; Gu, Tianwei; Hong, Ting; Liu, Jiayi; Sun, Jie; Wang, Hongdong; Bi, Yan; Zhu, Dalong
Highlights: This is the first description of circulating bile acid profiles in patients with PCOS. Serum conjugated primary bile acids are remarkably increased in PCOS patients. Conjugated primary bile acids are positively associated with serum total testosterone and androstenedione levels in PCOS. Abstract: Polycystic ovary syndrome (PCOS) is a common metabolic disorder with hyperandrogenism as the core pathophysiologic feature. Increased bile acids and altered bile acid pool composition have been implicated in the pathogenesis of several metabolic diseases. Thus, this study aimed to clarify the specific alterations in circulating bile acids in patients with PCOS and investigate its associations with hyperandrogenism. We recruited 37 patients with PCOS and 35 age- and BMI-matched control subjects. Serum bile acids and androgen profiles were assessed by ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS). Compared with control subjects, glycine- and taurine-conjugated primary bile acids were significantly elevated in patients with PCOS ( P  = 0.001 and P  < 0.001). In addition, these conjugated primary bile acids were significantly and positively associated with serum concentrations of total testosterone and androstenedione in the PCOS group. In conclusion, increased circulating conjugated primary bile acids are positively associated with hyperandrogenism in women with PCOS. Further studies are warranted to explore the underlying mechanism.